BRCA1/2 mutations appear embryo-lethal unless rescued by low (CGG n<26) FMR1 sub-genotypes: explanation for the "BRCA paradox"? - Andrea Weghofer (Public Library of Science (PLoS), 2012)
BRCA1/2 mutations and recently described constitutional FMR1 genotypes have, independently, been associated with prematurely diminished ovarian reserve. Whether they interrelate in distribution, and whether observed effects of BRCA1/2 and FMR1 on ovaries are independent of each other, is unknown. In a prospective comparative cohort study, we, therefore, investigated the distribution of constitutional FMR1 genotypes, normal (norm), heterozygous (het) and homozygous (hom), and of their respective sub-genotypes (high/low), in 99 BRCA1/2 mutation-positive women and 410 female controls to determine whether distribution patterns differed between study and control patients. In contrast to controls, BRCA1/2 carriers demonstrated almost complete absence of all constitutional FMR1 genotypes except for sub-genotypes with low (CGG (n<26)) alleles. Cross tabulation between BRCA1/2-positive patients and controls confirmed significant group membership, related to FMR1 distribution (P<0.0001). These results offer as most likely explanation the conclusion that BRCA1/2 mutations are embryo-lethal, unless rescued by low (CGG (n<26)) FMR1 sub-genotypes, present in approximately one quarter of all women. Women with low FMR1 sub-genotypes, therefore, should reflect increased BRCA1/2-associated cancer risks, while the remaining approximately 75 percent should face almost no such risks. If confirmed, this observation offers opportunities for more efficient and less costly BRCA1/2 cancer screening. The study also suggests that previously reported risk towards prematurely diminished ovarian reserve in association with BRCA mutations is FMR1-mediated, and offers a possible explanation for the so-called "BRCA paradox" by raising the possibility that the widely perceived BRCA1/2-associated tumor risk is actually FMR1-mediated.